Thyroid Hormone Coordination of Thermogenesis and Thermoregulation in Winter Passerines - Crisp, Alma (2023)
Small wild birds withstanding cold temperatures have to utilize efficient and diverse methods of heat production and regulation. Thyroid hormones (THs) contribute greatly to thermogenesis and thermoregulation through key pathways in birds, and are important to understand as temperatures change and the climate crisis forges onward. The purpose of this study was to investigate if there are differences in TH concentrations as they relate to ambient temperature in populations with different climates, as well as differences between two passerine species’ TH concentrations and trends in a single population. Wild great tits (Parus major) were captured and sampled from a northern population in Jyväskylä, Finland (coordinates: 62°36'57.2"N 26°20'48.8"E) and a southern population in Lund, Sweden (coordinates: 55°40'21.5"N 13°32'58.0"E). Blue tits (Cyanistes caeruleus) were captured from one northern population, along with great tits in Jyväskylä throughout the winter. Thyroid hormone concentrations were extracted from plasma and both T4 and T3 hormone isoforms were measured using Nano LC-MS/MS. Lund birds had significantly more T4 than Jyväskylä birds at similar temperatures, along with a steeper increase in hormone concentration with temperature than Jyväskylä birds. Differences in hormone concentrations were not found between species. T4 and T3 concentrations were positively correlated with ambient temperature, and negatively correlated with body temperature. These findings indicate population plasticity and flexibility in TH concentration in great tits. Although species differences were not found, due to size differences of the two species, similar TH concentration could be indicative of greater thermogenic needs in blue tits than great tits. This knowledge sheds new light on how small winter birds accommodate low temperatures, and can help predict their response to climate changes.